Learning Experiences of Postgraduate Students completing a course at the Hellenic Open University - Anna Tsiboukli; Katerina Kedraka; Niki Phillips (International Journal of Innovation and Research in Educational Sciences, 2018)
The present study focuses on adult trainees’ reflection upon their personal course of action and development on completing the five-year long post graduate program: “Adult Education” at the Hellenic Open University. Reflecting back, students where asked to evaluate their experience. It seems that learning within the research context is positively experienced. The positive aspects are relevant to how participants in this study managed to communicate with others when they were asked to express their own assumptions and reflect feelings and thoughts in a context of critical thinking and open dialogue.